(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
This article describes the comprehensive reforms in the livestock sector, one of the agricultural sectors in the Surkhandarya oasis. The article also reflects the creation of a legal framework for the development of farms and private farms in the agricultural sector in rural areas, as well as some measures taken in this area